How location-based social network applications are being used - Brennan, Sean (2015)
Location-based social network applications have globally become very popular with the expansion of smartphone usage. Location-based social networks (LBSN) can be defined as a site that uses Web 2.0 technology, GPS, WiFi positioning or mobile devices to allow people to share their locations, which is referred to commonly as a check-in, and to connect with their friends, find places of interest, and leave reviews or tips on specific venues. The aim of this study was to examine how location-based social applications are being used. The methods of this study comprised of a literature review and a discussion on prior research based on a selection of user studies on location-based social networks. This study also aimed at answering a number of sub-questions on user behavior such as activity patterns, motivations for sharing location, privacy concerns, and current and future trends in the field. Twelve LBSN user behavior studies were reviewed in this study. Eight of the user studies reviewed involved the application Foursquare. Research methods on eight of the reviewed studies were studies utilizing databases of the check-ins from the application itself or utilizing Twitter in their analysis. Four of the reviewed studies were user studies involving interviews and surveys. Three main themes emerged from the articles, which were activity patterns, motivations for sharing, and privacy concerns. It was found that activity patterns included common check-in venues such as restaurants, bars, shops, and entertainment venues along with the same times of day (early morning, lunchtime, and early evening) and having larger check-ins occur in urban areas. Motivations for sharing location showed that users share their location to showcase it to their friends and also to present one’s self. Concerning privacy, it was commonly found that users do not like to share their location with strangers. Future research could include looking at how gender, different age groups, and social media usage correlate with LBSN application usage in addition to how differences between iPhone and Android users correlate with it.